BAD EXPERIENCES, DRAG LEVELS AND SPORTS PARTICIPATION: DEMOGRAPHIC EVALUATION STUDIES AND CORROSIVE JUNIOR HIGHSCHOOL IN INDONESIA - Yugo Styawan; Titik Purwati; Ahmad Lani (UNIVERSITAS PGRI ADI BUANA SURABAYA, 2023)
The purpose of this study was to obtain information on negative experiences, levels of inhibition, and participation in sports based on the demographics of Indonesian junior high schools and the functional relationship between the three. The research method used is descriptive quantitative and correlational design with the design of the test using the discrepancy model. The sample consists of 1690 junior high schools in Indonesia. Data were analyzed using three techniques: one route re-route, two-reroute check and correlation analysis. Research shows that: 1) bad experiences exceed the established low tolerance threshold; 2) the drag level does not exceed the specified low tolerance limit; 3) training participation does not meet well defined criteria; and 4) correlation analysis concluded that there is a fairly strong positive correlation between experience and barriers to exercising. When bad experiences are high, sports problems are high. While the relationship between bad experiences with physical activity and the relationship between sports barriers and physical activity also correlates, the relationship is negative. These results indicate that the three variables influence each other. When the level of bad experience is low, the training barriers will also be low, so that it will affect the level of training participation.